Exponential Estimate for the Fundamental Matrix of a Linear Impulsive System - Petryshyn, R. I.; Sopronyuk Т. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We investigate the properties of oscillating sums and integrals dependent on parameters. These properties are used for the estimation of the normal fundamental matrix of a linear system with rapidly oscillating coefficients and pulse influence at fixed moments of time.